2011
DOI: 10.1021/mp200016d
|View full text |Cite
|
Sign up to set email alerts
|

Negatively Charged Liposomes Show Potent Adjuvant Activity When Simply Admixed with Protein Antigens

Abstract: Liposomes have been investigated extensively as a vaccine delivery system. Herein the adjuvant activities of liposomes with different net surface charges (neutral, positive, or negative) were evaluated when admixed with protein antigens, ovalbumin (OVA, pI = 4.7), Bacillus anthracis protective antigen protein (PA, pI = 5.6), or cationized OVA (cOVA). Mice immunized subcutaneously with OVA admixed with different liposomes generated different antibody responses. Interestingly, OVA admixed with net negatively cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 49 publications
0
39
0
Order By: Relevance
“…Based on this we were surprised that the anionic liposome formulation of GLA provided the greatest enhancement of ID93-specific TH1 responses, even though there was little detectable association with ID93. However another study found that anionic liposomes, such as the DPPG-containing liposomes used here, are effective adjuvant formulations despite lack of antigen association [43]. The mechanisms of this activity are unclear but may affect the site of vaccine injection or cells that traffic to the injection site and take up the antigen.…”
Section: Discussionmentioning
confidence: 99%
“…Based on this we were surprised that the anionic liposome formulation of GLA provided the greatest enhancement of ID93-specific TH1 responses, even though there was little detectable association with ID93. However another study found that anionic liposomes, such as the DPPG-containing liposomes used here, are effective adjuvant formulations despite lack of antigen association [43]. The mechanisms of this activity are unclear but may affect the site of vaccine injection or cells that traffic to the injection site and take up the antigen.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, OVA admixed with negative 1,2-dioleyl-sn-glycero-3-phosphatidic acid liposomes was as immunogenic as OVA admixed with positive 1,2-dioleoyl-3-trimethyl ammonium propane liposomes. The cOVA antigen showed comparable adjuvant activities in all liposomes [Yanasarn et al 2011]. Neutral phosphatidylcholine (PC)/cholesterol small unilamellar vesicles (SUV) also proved to be effective vaccine carriers.…”
Section: Liposome-based Antigensmentioning
confidence: 99%
“…Lipoplexes may also act as immuneadjuvant when admixed with protein antigens. However, their adjuvant activity is primarily due to enhanced uptake of proteins by antigen presenting cells as compared to negatively charged liposomes that promote activation and maturation of antigen presenting cells (128). Recent research has focused on making lipoplexes more plasma friendly, optimizing morphological features which can control cellular uptake and intracellular disposition (129)(130).…”
Section: Lipoplexesmentioning
confidence: 99%